ENT : Core Knowledge - Koltsidopoulos, Petros; Skoulakis, Charalampos; Kountakis, Stilianos (Springer International Publishing : Imprint: Springer, 2017)
This concise book summarises the basic knowledge required to be an otolaryngologist. It covers the 300 main ear, nose and throat diseases, summarizing the main symptoms of each disease, the required diagnostic process and the therapeutic approach. This compact presentation of knowledge is very useful and practical. The reader can quickly access essential information on the majority of the ENT diseases. ENT: Core Knowledge is ideal for ENT residents who are preparing for Board exams, for specialists who want to refresh and update their knowledge, and for general practitioners with a special interest in ENT. .
Keywords: Medicine.; Otolaryngologic surgery.; elektronické knihy; electronic books